2014
DOI: 10.1111/jvh.12373
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and endogenous cytokine levels in children with chronic hepatitis C

Abstract: Little is known about how hepatitis C (HCV) infection affects cognitive function in children. The aim of the study was to assess the impact of HCV infection on cognitive function of children with normal liver functions and their relationships to endogenous IFN-α, IL-6 and TNF-α. IFN-α, IL-6 and TNF-α were measured and the Arabic version of the Stanford-Binet test used to assess cognitive functions in 35 children with HCV infection and 23 controls. Serum levels of IL-6 and IFN-α were significantly higher in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…However, progression to significant fibrosis can occur, and cases of cirrhosis, hepatocellular carcinoma, and end‐stage liver disease requiring liver transplantation have been reported. In addition, quality of life and cognitive function may be compromised in children with HCV …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, progression to significant fibrosis can occur, and cases of cirrhosis, hepatocellular carcinoma, and end‐stage liver disease requiring liver transplantation have been reported. In addition, quality of life and cognitive function may be compromised in children with HCV …”
mentioning
confidence: 99%
“…In addition, quality of life and cognitive function may be compromised in children with HCV. (10)(11)(12) In children, the primary route of HCV infection is through perinatal transmission, with an approximate transmission rate from an HCV-infected mother of 5%. (13) In the presence of inadequately controlled human immunodeficiency virus (HIV ) coinfection or high HCV RNA viral loads (>6 log IU/mL) in the mother, transmission rates are as high as 14%.…”
mentioning
confidence: 99%
“…In children with viral hepatitis and hepatic encephalopathy due to acute liver failure, significantly lower scores on cognition tests were observed, both in acute and under more chronic conditions (IQ (mean ± SD) 61.8 ± 13.6 in children with chronic viral hepatitis vs 106.2 ± 12.8 in controls). (11,12) The results of children with acute liver failure normalized during follow-up, approximately five months after discharge, when the hepatic encephalopathy resolved. (11) Children suffering from chronic viral hepatitis, with normal liver function tests, obtained lower scores on vocabulary, total verbal relation, the bead memory test, total short-term memory, and IQ, in comparison to healthy controls.…”
mentioning
confidence: 99%
“…Some studies performed multiple regression analysis and reported higher scores on late postoperative (between three and ten years) achievement scales in patients who had a living-related donor in comparison to a cadaveric organ (8,26). In children with viral hepatitis and hepatic encephalopathy due to acute liver failure, cognitive test results were negatively correlated to elevated blood proinflammatory cytokines and liver changes on MRI (11,12). Furthermore, more impaired scores on cognition were reported in children after LTx for genetic-metabolic induced liver disease in comparison to children after LTx with BA or other cholestatic diseases, both before LTx and during follow-up (9,18,21).…”
mentioning
confidence: 99%
“…It is, however, interesting to note that in a larger study of HCV cognitive impairment, serum levels of interleukin 6 (IL‐6) and TNF‐α were related to poorer cognitive functioning . In another report, children with hepatitis C at an early stage of infection exhibited cognitive impairment that was associated with increased levels of interferon‐α and IL‐6 .…”
mentioning
confidence: 99%